Biological Cycle of Susceptible and Glyphosate-Resistant Sourgrass Biotypes in Two Growth Periods - FERREIRA,S.D. (2018)
ABSTRACT: Selecting glyphosate-resistant Digitaria insularis may cause changes in the biological cycle of the species. Therefore, the objective of this study was to evaluate the biological cycle of susceptible and glyphosate-resistant D. insularis biotypes in two growth periods (summer/autumn and autumn/winter). Seeds were collected in the municipality of Alagoa Grande (07o02’59" S 35o37’01,5" W), and were considered susceptible (S1), in Cascavel (24o55’27" S 53o27’54.6 ”W) considered as resistant 1 (R1), Entre Rios do Oeste (24o40’44" S 54o17’05" W) considered as resistant 2 (R2) and Marechal Cândido Rondon (24o42’30" S 54o21’10" W) considered as resistant 3 (R3). Evaluations were carried out in the summer/autumn and autumn/winter periods. The collection periods of plants were: 14; 21; 28; 35; 42; 49; 56; 63; 70; 77; 84; 91; 98; 105; 112 and 119 days after emergence (DAE). The selection of glyphosate-resistant D. insularis biotypes in agricultural areas affected the biology of the species, in relation to the original population of the susceptible biotype. In the summer/autumn period (mean temperature 24.6 oC), the S biotype started the emission of tillers and flowering at 14 and 21 DAE on an average, respectively, before the resistant biotypes. However, in the autumn/winter period (mean temperature 19.0 oC) only the R1 biotype was able to develop and complete the biological cycle. The evaluated biotypes presented differences during the development, mainly between the phenological stages, so that the susceptible biotype was the most precocious and with a high reproductive potential. The physiological evaluations showed no differences among the S, R1, R2 and R3 biotypes, as verified in the TCR.